Physicochemical Characterization and Phytochemical Screening of Citrus aurantifolia Lime Peel Ethanolic Extract from Kediri as Antibacterial Agent - Putri, Luluk Aniqoh Meliana; Febrianto, Yahya (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2023)
Citrus aurantifolia (Christm.) Swingle lime peel, widely discarded as agricultural waste in Kediri, East Java, Indonesia, is a promising source of bioactive compounds for antibacterial applications. Quality standardization of herbal materials is prerequisite for reproducible pharmacological activity, yet comprehensive physicochemical and microbiological characterization of lime peel simplicia from this region has not been reported. This study aimed to characterize the dried powder of C. aurantifolia lime peel collected from Kediri according to Indonesian Herbal Pharmacopoeia (IHP) standards, including microbial quality parameters (Total Aerobic Plate Count/ALT and Mold-Yeast Count/AKK), and to conduct phytochemical profiling of both simplicia and the ethanolic extract. Lime peels were cleaned, dried at 40–50°C, powdered, and characterized for water content (8.64%), water-soluble extract (26.67%), ethanol-soluble extract (18.14%), total ash (5.62%), acid-insoluble ash (0.35%), ALT (3.5 × 10³ CFU/g), and AKK (1.2 × 10² CFU/g)—all within IHP requirements. Phytochemical screening detected alkaloids, flavonoids, glycosides, saponins, tannins, and steroids/triterpenoids in both simplicia and extract. These findings establish a standardized pharmacognostic profile supporting the use of Kediri-sourced lime peel extract in evidence-based antibacterial research.